2013
DOI: 10.1186/1748-717x-8-237
|View full text |Cite
|
Sign up to set email alerts
|

Single arc volumetric-modulated arc therapy is sufficient for nasopharyngeal carcinoma: a dosimetric comparison with dual arc VMAT and dynamic MLC and step-and-shoot intensity-modulated radiotherapy

Abstract: BackgroundThe performance of single arc VMAT (VMAT1) for nasopharyngeal carcinoma (NPC) on the Axesse linac has not been well described in previous studies. The purpose of this study is to assess the feasibility of VMAT1 for NPC by comparing the dosimetry, delivery efficiency, and accuracy with dual arc VMAT (VMAT2), dynamic MLC intensity-modulated radiotherapy (dIMRT), and step-and-shoot intensity-modulated radiotherapy (ssIMRT).MethodsTwenty consecutive patients with non-metastatic NPC were selected to be pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 33 publications
0
20
0
2
Order By: Relevance
“…We cannot simply compare these results with ours, but assume that even if we make the IMXT plan with the VMAT technique, the dose to the oral cavity in A-IMPT plan would have been preferential to the adaptive VMAT plan. This is because low but de nite doses are irradiated to the entire oral cavity in the VMAT plan in the Ning et al 24 . study while the anterior part of the oral cavity was spared from any irradiation in the A-IMPT plan in all the patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot simply compare these results with ours, but assume that even if we make the IMXT plan with the VMAT technique, the dose to the oral cavity in A-IMPT plan would have been preferential to the adaptive VMAT plan. This is because low but de nite doses are irradiated to the entire oral cavity in the VMAT plan in the Ning et al 24 . study while the anterior part of the oral cavity was spared from any irradiation in the A-IMPT plan in all the patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…V TV is the treatment volume of the body received the prescribed dose, V PTV is the volume of PTV, and TV PV is the target volume covered by the prescribed dose. The lower the HI value means the better the homogeneity [17]. CI is normally used to quantitatively measure the conformality of the dose distribution relative to the target volume, which denotes the ratio of reference dose received by targets and normal tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have suggested that VMAT may be useful in a variety of treatment sites, such as BC [6][7][8] and NPC [9][10][11][12]. As well all known that high quality treatment plan relies on the skills and experience of the dosimetrist, which can vary greatly.…”
Section: Introductionmentioning
confidence: 99%